Managerial economics : tools for analyzing business strategy - Webster, Thomas J., 1949- (Lanham ; Boulder ; New York ; London : Lexington Books, 2015)
Each year, thousands of businesses file for bankruptcy protection because managers fail to efficiently organize the company’s operations, misread market trends, pay inadequate attention to product quality, or misinterpret the activities and intentions of rival companies. Perhaps they fail to formulate optimal advertising or financing strategies, procure raw materials and components at least cost, or provide adequate incentives to motivate workers to put forth their best efforts. Managerial economics is the application of economic principles to topics of concern to managers. This textbook develops a framework for predicting managerial responses to changes in the business environment. It combines the various business disciplines with quantitative methods to identify optimal solutions to more efficiently achieve a firm’s organizational objectives. The topics discussed in this textbook are readily accessible to students with a background in the principles of microeconomics and business mathematics. The selection and organizations of topics makes the textbook appropriate for use in a wide range of curricula by students with different backgrounds.
Publikace představuje komplexní přehled principů a analytických nástrojů manažerské ekonomie. Autor propojuje ekonomickou teorii s praktickými aspekty podnikové strategie a rozhodování. Kniha vysvětluje, jak lze pomocí mikroekonomických modelů, kvantitativních metod a analýzy trhu optimalizovat firemní cíle, řídit náklady a maximalizovat zisk. Důraz je kladen na aplikaci ekonomických nástrojů v reálných situacích podnikové praxe.
Terminologický slovník
Obsahuje bibliografické odkazy a rejstřík
Keywords: podniková ekonomika; strategický management; mikroekonomie; rozhodování; podnikový management; učebnice; monografie; managerial economics; strategic planning; microeconomics; decision making; industrial management; textbooks; monographs